The Maintenance Strategy for Optimizing Distribution Transformer Life Cycle Cost - Bo Ye; Lei Xuan; Bo Xu; Gefei Qiu; Zhangzhou He; Ming Li (Institute of Advanced Engineering and Science, 2013)
During the operation, the distribution transformer performance will deteriorate. The maintenance is an essential task in enhancing the safety of distribution transformer. Based on equal deterioration theory, the relationship among distribution transformer failure rate in each period of maintenance was deduced. After analyzing the maintenance costs and the failure costs in detail, the model of optimal life cycle costs for distribution transformer was established. Then the genetic algorithm was used to solve the model for obtaining the optimal maintenance strategy. Finally, the optimization results and the influence factors were analyzed. The results demonstrate the feasibility and validity of the proposed method. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3458